Islam dan Pemberontakan terhadap Status Quo: Telaah atas Pemikiran teologi Sosial Ali Syariati - Mukhlis Mukhlis (Ulumuna, 2009)
Ali Syariati, a Syiah moslem intellectual and a doctor in sociology of Islam, has written books and articles that are inspired by his Islamic internalization as a Syiah moslem. This article, through social theological perpective, is aimed at grasping sociological ideas of Syariati’s by tracing its theological and philosophical basis and his world view. It is found that his ideas are more an expression of islamic thought which are articulated in sociological terms. His ideas aimed to break the opressor-oppressed relation of Iran people at his time. The spirit of his ideas is to vanish the first and, then, awaken the second so that they are able to quit of the shackle of oppression. Those are responsible to do such a hard duty are rûshanfekr, enlightened intellectual. Qs. 28:5 and Qs. 30:1-4 and 30 are among al-Qur’an verses that inspired him and became theological arm rest of his ideas.